Transvaginal Cervical Screening in Individuals with Previous Late Preterm Birth - Aboukhater, Diana; Elzarea, Amira; Campbell, Shaida; Hatton, Wave; DeYoung, Tracey; Waller, Jerri; Kawakita, Tetsuya (American Journal of Perinatology, 2025)
This study aimed to assess the effectiveness of ultrasound cervical length (CL) screening in reducing preterm births among individuals with various preterm birth histories, aiming to optimize prevention strategies.This retrospective cohort study included 576 pregnant individuals with singleton pregnancies and a history of preterm birth, who underwent transvaginal ultrasound CL screening between January 2014 and December 2020. The primary outcome was the detection of a short cervix (≤2.5 cm). We compared outcomes among individuals with a previous gestational age (GA) of 34 to 36, 28 to 33, 24 to 27, and <24 weeks. Adjusted relative risks (aRRs) with 95% confidence intervals (95% CIs) were calculated using modified Poisson's regression with robust variance, controlling for predefined confounders.Of 576 (35%), 139 (24.1%) had a previous birth at 34 to 36 weeks, 129 (22.4%) had a previous birth at 28 to 33 weeks, 90 (15.6%) had a previous birth at 24 to 27 weeks, and 218 (37.8%) had a previous birth <24 weeks. Compared with individuals with a previous GA 34 to 36 weeks, the risk of short cervix was higher in those with a previous <24 weeks (21.6 vs. 52.8%, aRR = 2.56, 95% CI: 1.81–3.62) and GA 24 to 27 weeks (40.0%, aRR = 1.80, 95% CI: 1.20–2.71), but no difference was found with those with previous GA 28 to 33 weeks (24.8%, aRR = 1.12, 95% CI: 0.72–1.72). Compared with individuals with previous GA 28 to 33 weeks, individuals with prior GA 34 to 36 weeks had the same risk of cerclage placement and preterm birth <34 weeks, but a lower risk of composite neonatal outcomes.Based on our results of similar incidence of the short cervix between individuals with previous GA 34 to 36 weeks and those with previous GA 28 to 33 weeks, individuals with a history of late preterm birth should receive CL screening in a similar manner.
Keywords: cervical cerclage; cervical length screening; gestational age; neonatal outcomes; preterm birth; transvaginal ultrasound